2014
DOI: 10.1111/cpr.12105
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization and osteoblast response to a functionally graded hydroxyapatite/fluoro‐hydroxyapatite/titanium oxide coating on titanium surface by sol–gel method

Abstract: Current results indicated that the novel TiO2 /FHA/HA coating has promising clinical applications in orthopaedic and dental implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Many researchers suggested that the anatase had better bioactivity than rutile because of its apatite-forming ability and 33 34 number of hydroxyl groups. [35][36][37] In this experiment, results showed that the anatase phase formation between 400 C and 600 C agreed with previous literatures. When the annealing temperature was 400 C, the anatase XRD affrication peak was small.…”
Section: Effect Of Drying Temperature On Characterization Of Tio 2 Filmssupporting
confidence: 92%
“…Many researchers suggested that the anatase had better bioactivity than rutile because of its apatite-forming ability and 33 34 number of hydroxyl groups. [35][36][37] In this experiment, results showed that the anatase phase formation between 400 C and 600 C agreed with previous literatures. When the annealing temperature was 400 C, the anatase XRD affrication peak was small.…”
Section: Effect Of Drying Temperature On Characterization Of Tio 2 Filmssupporting
confidence: 92%
“…Additionally, it is possible by MAO to obtain the formation of TiO 2 in the form of anatase and rutile . Some authors had stated that TiO 2 with structures of anatase and rutile induced the apatite formation in vitro . Kunzler et al developed a surface modification process to develop roughness gradients ranging from 1.0 to 5.7 μm on Ti surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Methods used for coating metal implants with HAp include plasma spray [297][298][299][300][301], electrophoretic deposition [302][303][304][305], pulsed laser deposition [306][307][308][309], sol-gel deposition [310][311][312][313][314], spin-coating [290], sputtering techniques [315][316][317], ion assisted deposition [296,318,319], and many other techniques such as immersion, hot pressing and hot isostatic pressing, thermal spraying and electrostatic spraying [320,321]. Plasma spraying technique is one of the most economical methods.…”
Section: Coating Of Implantsmentioning
confidence: 99%